2010
DOI: 10.5120/1295-1783
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Classification of Remotely Sensed Satellite Data using Bayesian and Hybrid classifier

Abstract: In this paper an attempt has been made to develop classification algorithm for remotely sensed satellite data using Bayesian and hybrid classification approach. Bayesian classification is a probabilistic technique which is capable of classifying every pattern until no pattern remains unclassified. Hybrid classification involves developing training patterns using unsupervised classification followed by classifying the pixels using supervised classification. It is observed that the overall accuracy was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The land-cover map was classified to estimate the biomass and carbon stock for each class using Erdas software. The classifications including DEF, MDF, DDF, DF, and PFi with trees were analyzed using a hybrid classification technique that uses both supervised and unsupervised classifications with GIS [34,51]. The hybrid classification involved developing training patterns via the use of an unsupervised classification followed by a supervised classification [51].…”
Section: Land-cover Classification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The land-cover map was classified to estimate the biomass and carbon stock for each class using Erdas software. The classifications including DEF, MDF, DDF, DF, and PFi with trees were analyzed using a hybrid classification technique that uses both supervised and unsupervised classifications with GIS [34,51]. The hybrid classification involved developing training patterns via the use of an unsupervised classification followed by a supervised classification [51].…”
Section: Land-cover Classification Methodsmentioning
confidence: 99%
“…The classifications including DEF, MDF, DDF, DF, and PFi with trees were analyzed using a hybrid classification technique that uses both supervised and unsupervised classifications with GIS [34,51]. The hybrid classification involved developing training patterns via the use of an unsupervised classification followed by a supervised classification [51]. For the unsupervised classification, a K-means clustering algorithm was used to search for natural groups of pixels called clusters, which were located in the data by assessing the relative locations of the pixels in the feature space for separations between vegetation and non-vegetation classes.…”
Section: Land-cover Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the imagery processing was performed by Idrisi software (Taiga version). We took advantage of both the supervised (Maximum likelihood algorithm) and unsupervised (Kmeans clustering algorithm) classification methods for producing the land use map (Pradhan et al 2010). The land use map in our study included 6 classes: forest, rangeland, A c c e p t e d M a n u s c r i p t 5 cropland, rocks, urban area and roads.…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…(Perumal and Bhaskaran 2010) compared hard classifiers (parallelepipe, minimum distance, maximum likelihood, and Mahalanobis) with some advanced classifiers like an artificial neural network, and spectral angle mapper and concluded that Mahalanobis classifier performed optimally. Similarly, (Pradhan et al 2010) classified land use/ land cover using Bayesian and Hybrid classifiers and observed 91.57% using hybrid and 90.53% using the Bayesian classifier. It was clear that none of these classifiers of remotely sensed data has been applied in any part or the whole of Andoni L.G.A.…”
Section: Introductionmentioning
confidence: 99%